Differentiation of Fourier Series via Orthogonal Derivative - Cruz-Santiago, R.; López-Bonilla, J.; López-Vázquez, R. (Journal of Institute of Science and Technology, 2015)
It is very known that if the operator d/dx acts on each term into a convergent Fourier Series (FS), then it may result a divergent series. This situation is remedied applying the symmetric derivative to FS, which implies the existence of the important Fejér-Lanczos Factors. In this paper, we show that the orthogonal derivative also leads to these Factors. Journal of Institute of Science and Technology, 2015, 20(2): 113-114